ACIS UiTM meterai perjanjian persefahaman (MoU) bersama Japan Muslim Foundation Nippon Muslim Corporation Universitas Wiralodra - UiTM, Akademi Pengajian Islam Kontemporari (Akademi Pengajian Islam Kontemporari, UiTM, 2020)
13 NOVEMBER 2020 - Universiti Teknologi MARA (UiTM) had recently signed a Memorandum of Understanding (MoU) with the Japan Muslim Foundation, Nippon Muslim Corporation and Universitas Wiralodra, Indonesia (UNWIR). The event was successfully held at Level 7, Tuanku Syed Sirajuddin Chancellery Building, UiTM Shah Alam.The MoU was signed by the Vice Chancellor UiTM, YBhg. Prof. Emeritus Datuk Ir. Dr. Mohd Azraai Kassim. Mr. Zulkarnain Hasan Basri as President and Chief Executive Officer (CEO) has signed the MoU on behalf of Japan Muslim Foundation and Nippon Muslim Corporation. Dr. Ujang Suratno, SH., M.Si, Rector of Universitas Wiralodra has signed the MoU on behalf of the university. The MoU was witnessed by Prof. Madya. Dr. Nurhidayah Muhammad Hashim (Dean of ACIS), Kimata Afiq (General Manager of Japan Muslim Foundation), Kimata Kyoko (Director of Nippon Muslim Corporation) and Mr. H. Ibnu Rusydi, MA (Dean Faculty of Islamic Studies UNWIR).